Major and minor head losses in a hydraulic flow circuit: experimental measurements and a Moody’s diagram application - Amaral Madeira, Aline (Eclética Química, 2020)
Domestic and industrial hydraulic drainage networks have gradually become more complicated because of the cities’ rapid expansion. In surcharged hydraulic systems, the head losses may become rather significant, and should not be neglected because could result in several problems. This work presents an investigation about major and minor head losses in a hydraulic flow circuit, simulating the water transport in a drainage network at room temperature (298.15 K) under atmospheric pressure (101,325 Pa). The losses produced by the fluid viscous effect through the one used cast-iron rectilinear pipe (RP-11) and the localized losses generated by two flow appurtenances, one fully open ball valve (BV-1) and one module of forty-four 90º elbows (90E-8) were experimentally measured. Experimental data generated head-loss curves and their well fitted to potential regressions, displaying correlation coefficients (R2) of 0.9792, 0.9924, and 0.9820 for BV-1, 90E-8, and RP-11, respectively. Head loss experimental equations and local loss coefficients through BV-1 and 90E-8 were determined successfully. The Moody’s diagram application proved to be a quite appropriate tool for an approximate estimation of Darcy-Weisbach friction factor. A good approximation between friction factor values obtained via experimental measurements and the Moody’s diagram was observed with mean absolute deviate of 0.0136.